Salmonella Epidural Abcess with Acute Paraplegia: Report of a Rare Vertebral Infection - Carvalho, Ajay S; Jain, Atul; Dey, Subir; Sengupta, Sudip K (Nepal Journal of Neuroscience, 2023)
Salmonella Vertebral osteomyelitis (SVO) is an uncommon entity. In this article, we reported a rare case of a 39-year-old man admitted with low backache for three days which progressed to paraparesis within 24 hours. Urgent CEMRI revealed Spondylodiscitis D7/D8 associated with an epidural abscess causing significant cord compression. He was initially diagnosed as thoracic Potts Spine and underwent emergency decompressive surgery. He was started on Antitubercular drugs, however, tissue and wound culture grew Salmonella Enterica. USG abdomen revealed hepatosplenomegaly. He was started on 6 weeks intravenous antibiotics accordingly; the patient showed postoperative improving neurological deficits with significant symptomatic relief and radiological resolution.